Orthodoxy and fundamentalism contemporary perspectives - ǅalto, Davor 1980-; Demacopoulos, George E. 1970- (Lexington Books/Fortress Academic, 2022)
"This book brings together twelve essays by some of the leading scholars on Orthodox Christianity on the issue of fundamentalism and religious Orthodoxy in the contemporary world"--
Keywords: Orthodox Eastern Church / Doctrines; Fundamentalism; Fondamentalisme; Orthodox Eastern Church; Theology, Doctrinal